An inland population of Azorina vidalii (Watson) Feer at Faial Island. - Schäfer, Hanno (1999)
An inland population of Azorina vidalii (Watson) Feer (Campanulaceae) near Capelo, Faial island, and the special habitat are described. The origin is discussed.